Justiça de Deus e justificação: estudo exegético de Rm 1,16-17 - Paz, Roberto Almeida da (2015)
The present study focuses on the hermeneutics of justice and justification, whose emphasis is the Letter to the Romans. It aims at bringing out the substantial content of justification by faith in Pauline theology, within the studied pericope (Rom 1,16-17). Then it examines the consequences of the justication s intelligibility, as the principle of salvation of man (Jew and Greek) through gratuity and divine initiative. The objective is to understand the notion of justification in order to detect its conceptual structure and theological concepts to which it relates, such as justice, gospel, faith, reconciliation, salvation, etc. In addition, the exegetical path used here presents a thorough study of Paul s understanding, which justifies man by his faith in Christ and the Holy Spirit. The conclusion suggests some reflections regarding the contemporaneity of the topic, rather than a hasty understanding that justification might essentially stem from Protestant theology